Negosiasi Identitas Komunitas Punk Bogor Dalam Masyarakat Dominan - Makarim, Nabil; Rahardjo, Turnomo; Qurrota Ayun, Primada (Interaksi Online, 2024)
The punk community, is a community that is included in the marginalized group in society because punk culture is a culture adopted from outside that has a different appearance from society in general and carries an ideology of resistance to the dominant culture, so that the punk community is often faced with a negative stigma from society associated with criminality and other negative things, and also the misconception of meaning by individuals in punk who commit negative actions and further muddy the name of punk in Indonesia. This research aims to find out the efforts made by the Bogor punk community in negotiating its identity to the dominant or majority society. This research uses the co culture theory proposed by Mark Orbe. This descriptive qualitative research was conducted using a phenomenological approach that focuses on the experiences of informants, researchers use data collection techniques with indepth interviews. The results of the study show that the Bogor punk community still fights against capitaslime and criticizes all forms of injustice in society, but they fight in a more positive way this is done because they want to change the negative stigma that exists in society. In negotiating the identity of the punk community using accommodation communication where they try to establish a positive relationship with society. The marginalization obtained by the Bogor punk community does not make them feel marginalized, instead they are able to survive and manage their identities well and are able to control emotions when they get marginalized by society. It can be described that they have no purpose or desire to disturb public order. Instead, they often do positive activities such as social activities to help people who are more in need.